Case Report: Simultaneous Hyperprogression and Fulminant Myocarditis in a Patient With Advanced Melanoma Following Treatment With Immune Checkpoint Inhibitor Therapy - Barham, Whitney; Guo, Ruifeng; Park, Sean S.; Herrmann, Joerg; Dong, Haidong; Yan, Yiyi (Frontiers in Immunology, 2021)
We report here a patient with stage IV mucosal melanoma treated with dual immune checkpoint inhibitor (ICI) therapy (Nivolumab/Ipilimumab) who experienced rapid disease progression and metastatic spread within three weeks of first infusion. Surprisingly, this patient also developed fulminant myocarditis within the same time frame. Immunohistochemical staining of the primary tumor and a metastatic omental lesion revealed robust CD8+ PD-1+ T cell infiltration after ICI treatment, as would be expected following immune activation. However, the CD8+ T cell infiltrate was largely negative for both Granzyme B and TIA-1, suggesting these T cells were not capable of effective tumor lysis. We discuss the possibility that heightened pro-inflammatory T cell activity (rather than tumor-directed cytolytic activity) was induced by anti-PD-1 and anti-CTLA-4, which could have provoked both rapid tumor resistance mechanisms and myocarditis. This case highlights the fact that the mere presence of tumor infiltrating lymphocytes (TILs) does not necessarily correlate to ICI response and that additional functional markers are necessary to differentiate between inflammatory and cytolytic CD8+ TILs.